(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Teaching and learning based on heutagogical strategies is one of the current learning methods in an effort to improve learning strategies in Institutions of Higher Learning (IPT). In line with the 21st century learning approach, this heutagogy strategy focuses on self-determined learning by students and lecturers as facilitators so that students have the knowledge, talent and ready to enter the world of career. Today, the reliance of students on lecturers entirely in the acquisition of knowledge is less relevant, moreover the attitude of generation z students today who like things that are quick, easy and flexible should be celebrated positively by providing strategies that enable students to co- similarly planning learning. However to date heutagogical strategies (self -determination learning) by students occur less systematically and are not clear in existing learning activities. This study is to examine the need for learning methods based on heutagogical strategies (self -determination learning) from the perception of IPT lecturers. This study is qualitatively using a case study design. A total of twelve (12) lecturers from nine (9) public universities representing research universities, comprehensive universities and focus universities were the informants of the study. Study data were analysed manually based on thematic analysis using colour coding for each theme. The findings of the study found three main themes needed to implement heutagogical strategies in learning, namely the planning of implementation methods, commitment and readiness of students, support and learning activities. The method of teaching and learning using heutagogical strategy is a self -skill of students that need the guidance of lecturers and it is a continuous process that is constantly receiving changes and improvements in line with the needs and desires of the vision of Malaysian education. The findings of this study can be used as a guide in building a model of heutagogy (self -determination learning) in which learning in the 21st century vv has undergone change after change to adapt to the current situation where some learning activities are implemented virtually. In addition, the findings of this needs analysis can provide exposure to the higher education community, especially lecturers and students in realizing the aspirations of higher education, namely the transformation of higher education delivery and holistic graduates.